On the Moore Formula of Compact Nilmanifolds - Hamrouni, H. (Symmetry, Integrability and Geometry: Methods and Applications, 2009)
Let G be a connected and simply connected two-step nilpotent Lie group and Γ a lattice subgroup of G. In this note, we give a new multiplicity formula, according to the sense of Moore, of irreducible unitary representations involved in the decomposition of the quasi-regular representation IndΓG(1). Extending then the Abelian case.